Death and the afterlife in Syriac Christianity: creating social identity and emotional communities - Doerfler, Maria (Cambridge University Press, 2026)
In late antiquity as in the present age, death left its mark on the lives of families, communities, and societies. Syriac funerary hymns provide important insights into the social, emotional, funerary ritual histories of early Christian communities. Maria Doerfler here explores this body of largely ignored literature that has been attributed to Ephrem the Syrian. Different parts of the collection focus on individuals from a variety of social and ecclesiastical backgrounds: women and children, clergy and ascetics, as well as those who fell victim to natural disasters. The hymns provide insights not only into Syriac Christian ideas about death and the afterlife, but also into their existence, beliefs, and practices more broadly. Through engagement with different theoretical lenses, Doerfler uses instances of personal and communal crisis to elucidate historical and philosophical patterns among late antique Christians, addressing, inter alia, their responses to pandemics, understanding of wealth, and forging communal bonds that transcended death.